2004
DOI: 10.1148/radiol.2331030863
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Carotid Arteries in Symptomatic Patients: Cost-effectiveness of Diagnostic Strategies

Abstract: Duplex US performed without additional imaging is cost-effective in the selection of symptomatic patients suitable for endarterectomy. Adding MR angiography increases effectiveness slightly at disproportionately high costs, whereas DSA is inferior because of associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 25 publications
2
74
2
3
Order By: Relevance
“…Out of a total of 12 full cost-effectiveness studies that were identified as potentially relevant, four studies were deemed suitable for inclusion in the review: Wardlaw and colleagues, 5,26 Buskens and colleagues, 284 and Tholen and colleagues. 285 Among the eight not considered relevant, one study by the Centre for Evidence-based Purchasing published in 2008 105 concluded that there was no information on which to base a cost-effectiveness assessment of DWI in TIA/minor stroke, and was not considered further.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of a total of 12 full cost-effectiveness studies that were identified as potentially relevant, four studies were deemed suitable for inclusion in the review: Wardlaw and colleagues, 5,26 Buskens and colleagues, 284 and Tholen and colleagues. 285 Among the eight not considered relevant, one study by the Centre for Evidence-based Purchasing published in 2008 105 concluded that there was no information on which to base a cost-effectiveness assessment of DWI in TIA/minor stroke, and was not considered further.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Buskens and colleagues 284 examined the cost-effectiveness of non-invasive strategies in patients with TIA or minor stroke suspected of having carotid artery stenosis (CAS). The non-invasive strategies in this study included DUS, MRA and the two examinations combined; all were compared against intra-arterial digital subtraction angiography (DSA), which was the reference standard.…”
Section: Cost-effectiveness Analyses Of Imaging In Strokementioning
confidence: 99%
“…33 The annual costs of care for disabled patients after preventive treatment or SAH were taken from data on long-term care in stroke patients. 34 The model does not account for any costs of diagnostic follow-up in the notreatment arm. All cost estimates were updated to 2005 Euros based on Dutch inflation indices (http://statline.cbs.nl).…”
Section: Methods Model Structurementioning
confidence: 99%
“…Digital subtraction angiography is still occasionally necessary as an arbiter when the results of noninvasive procedures and the clinical diagnosis are not concordant. Results from cost-effectiveness studies 51,52 showed that duplex sonography as a single examination strategy was both less expensive and more effective than nearly all other strategies, including DSA. The combination strategy of CDDS and MRA has a slight benefit in clinical outcome but at extremely high additional costs, in which DSA is inferior for the associated complications.…”
Section: Comparison Of the Diagnostic Value Of Color Duplex Sonographmentioning
confidence: 99%
“…The combination strategy of CDDS and MRA has a slight benefit in clinical outcome but at extremely high additional costs, in which DSA is inferior for the associated complications. [51][52][53] The main drawback of CDDS is the high dependence on technological factors in both performance and interpretation. For the operator to be familiar with the baseline, about 200 examinations are needed, and a considerable larger number are needed for reliable grading of ICA stenosis and knowledge of pitfalls and limitations of the examination.…”
Section: Comparison Of the Diagnostic Value Of Color Duplex Sonographmentioning
confidence: 99%